"Territorial Peace": The Emergence of a Concept in Colombia's Peace Negotiations. Issue 2 (3rd April 2018) - Cairo, Heriberto; Oslender, Ulrich; Piazzini Suárez, Carlo Emilio; Ríos, Jerónimo; Koopman, Sara; Montoya Arango, Vladimir; Rodríguez Muñoz, Flavio Bladimir; Zambrano Quintero, Liliana
ABSTRACT: The essays collected in this forum discuss the political geography of the recent Colombian Peace Agreements, which aim to put an end to one of the most long lasting armed conflicts in Latin America. Central to many arguments in this accord is the concept of "territorial peace". From a range of different academic disciplines and perspectives, the authors of this Forum explore this concept, focusing on its genealogy during the period of peace negotiations (2012-2016), its importance in the content of the agreement, and some of its connected dimensions, in particular to notions of ethno-territorial, sex and gender issues, as well as formal party politics.